2017
DOI: 10.1007/s10008-017-3512-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical analysis of gildings in Valencia altarpieces: a cross-age study since fifteenth until twentieth century

Abstract: The application of the voltammetry of microparticles methodology to the study of gildings in paintings and architectural ornaments is described. Nanosamples from pieces from different churches of the Comunitat Valenciana (Spain) covering since the 15th century until nowadays were studied upon attachment to graphite electrodes in contact with aqueous HCl and H2SO4 electrolytes. Electrochemical measurements, combined with field emission scanning electron microscopy-X-ray microanalysis (FESEM-EDX) and atomic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…In order to investigate the possibility of monitoring voltammetrically the aging of works of art and suggesting the possibility of establishing electrochemical criteria for dating, Ferragud et al 66 reported on the application of VMP for studying gildings in samples from gilded surfaces of a series of altarpieces from the Comunitat Valenciana (Spain). The voltammetric response of submicrosamples of gilded panels from altarpieces attached to graphite electrodes in contact with HCl and H 2 SO 4 aqueous electrolytes was compared with that of polycrystalline gold electrodes.…”
Section: Voltammetry Of Microparticlesmentioning
confidence: 99%
“…In order to investigate the possibility of monitoring voltammetrically the aging of works of art and suggesting the possibility of establishing electrochemical criteria for dating, Ferragud et al 66 reported on the application of VMP for studying gildings in samples from gilded surfaces of a series of altarpieces from the Comunitat Valenciana (Spain). The voltammetric response of submicrosamples of gilded panels from altarpieces attached to graphite electrodes in contact with HCl and H 2 SO 4 aqueous electrolytes was compared with that of polycrystalline gold electrodes.…”
Section: Voltammetry Of Microparticlesmentioning
confidence: 99%
“…These methods exploit the high sensitivity of the voltammetry of immobilized particles (VIMP) [ [9], [10], [11]], a solid state electrochemistry technique that provides sensitive responses restricting the sampling to only a few nanograms collected on the metal surface by means of graphite leads [12,13]. Based on this methodology, widely used in the analysis of archaeological, historic and art objects in the science of conservation and restoration field [14,15], and primarily proposed as applicable to date ceramic materials [16], chronological information on lead-bronze statuary [17] and coinage [18], gold altarpieces [19] and embroidery [20] has been made available.…”
Section: Introductionmentioning
confidence: 99%
“…It is pertinent to underline that, by reasons of conservation, the sampling (consisting of pressing a graphite electrode onto the surface of the objects, as previously applied [ [14], [15], [16], [17], [18], [19], [20]]) was limited to three spots in each archaeological object. As a result, we obtained three replicate voltammetric measurements for each sample/object.…”
Section: Introductionmentioning
confidence: 99%